The art of found objects : interviews with Texas artists - Bunch, Robert Craig, 1954-; Bunch, Robert Craig, 1954- (Joe and Betty Moore Texas art series ;, 2016)
In this first book of interviews with visual artists from across Texas, more than sixty artists reflect on topics from formative influences and inspirations to their common engagement with found materials. Beyond the art itself, no source is more primary to understanding art and artist than the artist's own words. After all, who can speak with more authority about the artist's influences, motivations, methods, philosophies, and creations? Since 2010, Robert Craig Bunch has interviewed sixty-four of Texas' finest artists, who have responded with honesty, clarity, and-naturally-great insight int.